Integrating 3,4-Dihydro-2H-1,4-oxazine into peptides as a modification: silver triflate-catalyzed cyclization of N-Propargyl N-Sulfonyl amino alcohols for SPPS applications - Patil, Abhijit Ramchandra; Marelli, Udaya Kiran (Organic Letters, 2024)
We present a methodology yielding 3,4-dihydro-2H-1,4-oxazine by cyclization of N-propargyl N-sulfonyl amino alcohols using silver triflate as a catalyst at ambient temperature. Additionally, we showcase the applicability of this methodology in solid phase peptide synthesis (SPPS) to introduce the oxazine heterocyclic ring into short peptides containing serine and threonine. Notably, Rink amide resin supported the on-resin formation of 3,4-dihydro-2H-1,4-oxazine, while 2-CTC resin facilitated the oxazine formation in a one-pot process involving peptide cleavage, deprotection, and subsequent C-O ring formation, thus offering a versatile method for the late-stage modification of peptides.